Educational Program on Converting Plastic Waste into Alternative Fuel Using Pyrolysis and Triboelectric Nanogenerators (TENG) for Community Leaders in Kasomalang Kulon Tourism Village, Subang Regency - Hayadi Hamuda; Lukman Medriavin Silalahi; Safrizal Safrizal; Cahyono Budy Santoso; Yunus Widjaja; Chaerul Anwar; Teddy Mohamad Darajat; Listiana Satiawati; Sumihar M.L. Tobing; Aditiameri Aditiameri (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
This Community Service (CS) initiative was executed collaboratively by faculty members from five universities—Universitas Pamulang, Universitas Presiden, Universitas Trisakti, Universitas Pembangunan Jaya, and Universitas Borobudur—in Kasomalang Kulon Tourism Village, Subang Regency, West Java, on April 17, 2026. This initiative aimed to instruct village leaders, as prospective catalysts for change in waste management and renewable energy, on the technique for converting plastic trash into pyrolysis-derived alternative fuel and the Triboelectric Nanogenerator (TENG) energy harvesting technology. This activity addresses the critical issues of plastic waste pollution and the exhaustion of fossil fuel reserves. Annually, almost 8 million tonnes of plastic waste infiltrate the oceans, yet merely 9% of all plastic ever manufactured is effectively recycled. The collaborative effort encompassed Electrical Engineering, Computer Systems, Petroleum Engineering, Information Systems, Product Design, and Agrotechnology. The instructional techniques employed comprised lectures and conversations. The activity's results indicated that participants acquired a thorough comprehension of pyrolysis mechanisms, the principles of TENG energy conversion, and its possible applications at the village level. Despite the absence of direct implementation, the cadres shown significant motivation to facilitate technology adoption inside their communities. This PKM model demonstrates that interdisciplinary collaboration across universities is effective in providing innovative technological education to rural populations.